In the Clear Sky: The Cosmology of the Stars (Global Journal of Science Frontier Research, 2012)
In the universe that we live, in we are surrounded by trees, plants, animals, our human beings, oxygen and various other gases that make up the atmosphere. The Milky Way of the universe comprises planets, the moon, and the sun; which is a star like the other stars in the universe. This article looks at the stars within our universe and serves to inform and emphasise their role and formation to, astronomists, astrophysicists, cosmologists and, the general reader who are interested to know more about the cosmology of the stars.
Keywords: Milky Way; Constellation; Nebula; Galaxy; Gaseous Cloud; Nuclear Fusion; Gravitational force; Hydrostatic support; Cosmology